A Virtual Reality Approach to Personal Safety and the Design of Built Environment Facilities - Cozens, Paul; Greive, Shane (2002)
The Suzy Lamplugh Trust Research Institute at the University of Glamorgan is conducting research that focuses on personal safety issues as they relate to the design and maintenance of built environment facilities. The project, funded by Valley Lines (a network of 66 railway stations in South Wales) seeks to investigate the perception and reality of personal safety (against crime and nuisance, as opposed to health and safety) on these stations and their immediate access routes and environments. Customer satisfaction surveys have consistently reported that although recorded incidents of crime and nuisance are relatively low, rail users perceive their risk to be significantly higher and therefore discourages people from using the trains. The project uses interactive virtual reality (VR) scenes as the environmental stimuli for investigating perceptions. VR ‘walkthroughs’ of a sample of stations have been shown to focus groups representing samples of users and potential users. The standardisation of the ‘personal journey’ to, from and through the station represented by this approach and its ‘dynamic’ (rather than static) and interactive nature, make it a realistic avenue for evaluating how people decode the railway environment in personal safety terms. A pilot study for three stations was very encouraging and illuminating. The respondents provided a rich source of data, concerning their personal safety concerns in and around the station environment and the findings broadly support Crime Prevention Through Environmental Design (CPTED) theory. It also highlights the crucial importance of user perceptions in the design and management of built environment facilities. This methodology will also be employed to investigate perceptions of personal safety within the University campus environment, its immediate environment and access routes. Within this community, fear of crime has been shown to exist in locations where, according to recorded statistics, crime is low. Therefore, the objective is to develop applied solutions to improve personal safety on the campus. Finally a package of recommended solutions and a generic model shall be developed that can analyse problems and generate solutions to any campus University.